Use of sustainability indicators in rural properties: a methodological experience in the training of professionals of Agrarian Sciences (Research, Society and Development, 2020)
The search for sustainability guides several sectors of society, but its effectiveness may seem utopian and inconsistent with the economic and social factors of today's society. Understanding applicable concepts to the current reality, in its simple exercise, may constitute a path to its effectiveness. The experience involved 30 rural properties into Western Santa Catarina and was developed by the students of the undergraduate course in Animal Science of State University of Santa Catarina - Center for Western Studies - UDESC/CEO, campus of Chapecó. Using the MESMIS methodology, students considered different parameters for the measurement of sustainability indicators in each property, considering the environmental, social and economic dimensions. The maximum scores obtained were concentrated in the economic dimension and the minimum in the social one. The study, in addition to its didactic purpose, pointed out the severity of social conditions in the field (recurrent in studies of succession and aging), as well its lack of training and leisure spaces.